2008
DOI: 10.1103/physrevb.77.020101
|View full text |Cite|
|
Sign up to set email alerts
|

Theoretical study of the structure of calcium in phases IV and V viaab initiometadynamics simulation

Abstract: We searched for the structure of calcium in phases IV and V by a metadynamics simulation based on ab initio calculations, and found two structures. One is a tetragonal lattice which consists of two helical chains along the c axis. The other is an orthorhombic lattice of four zigzag chains. We have calculated the x-ray diffraction patterns and enthalpies of the two structures discovered by our simulation. From comparisons of the patterns with the experimental x-ray patterns of the phases IV and V and from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…We reproduced also the results of Ishikawa et al (18). At the pressure of 77 GPa the cP1 structure undergoes a transition to Ca-IV with a volume collapse of 3.5%, which in turn transforms Ͼ115 GPa into Ca-V phase with a volume collapse of 1%.…”
Section: Resultssupporting
confidence: 85%
“…We reproduced also the results of Ishikawa et al (18). At the pressure of 77 GPa the cP1 structure undergoes a transition to Ca-IV with a volume collapse of 3.5%, which in turn transforms Ͼ115 GPa into Ca-V phase with a volume collapse of 1%.…”
Section: Resultssupporting
confidence: 85%
“…In conclusion, whereas many structures, typically with larger unit cells of 4-8 atoms per cell, have been proposed (12)(13)(14)(15)17) to have lower zero-temperature enthalpies than sc, Ca remains in its simplest form with one atom per primitive unit cell. Given the rh to pm transition at low T, it is clear that at 300 K, anharmonic and entropic contributions play a significant role for the stabilization of the sc-like rh phase.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3 shows that in the pressure range 100-130 GPa there are several energetically extremely close structures, and the most stable structure at 89-116 GPa is the P4 3 2 1 2 − 8 structure proposed by Ishikawa et al (20), this structure also can be derived from sc by a large distortion and has recently been experimentally confirmed for Ca-IV phase (25). The Pnma-4 structure is the stable phase at higher pressures, 116-134 GPa, and is the last stable structure related to sc.…”
Section: Results Of Evolutionary Simulations: New Phases Of Calciummentioning
confidence: 99%
“…Whereas the sc phase is already superconducting, the most intriguing high Tc values are found in the stability fields of other phases; a recent x-ray diffraction study (2) found two further phases beyond sc-Ca-IV (stable at 113-139 GPa) and Ca-V (stable above 139 GPa). First structural models, proposed in (20), gave a structure possessing the P4 3 2 1 2 space group and 8 atoms in the unit cell (here denoted as P4 3 2 1 2-8) for Ca-IV and Cmca-8 for Ca-V. The P4 3 2 1 2-8 structure, proposed for Ca-IV, has indeed been confirmed experimentally (21).…”
mentioning
confidence: 82%
See 1 more Smart Citation